Axial Piston Pump Modelling: Use CFD and Neural Network Methods to Estimate the Performance Degradation Due to Internal Parts Deficiency - Akier, Dr.Amer Hussein (Aljameai, 2025)
Abstract: Axial piston pumps are critical components in hydraulic systems, known for their high efficiency and ability to operate under high-pressure conditions. However, performance degradation over time due to internal part deficiencies, such as wear, leakage, and cavitation, remains a significant challenge. This paper proposes a combined approach using Computational Fluid Dynamics (CFD) and Neural Network (NN) methods to estimate the performance degradation of axial piston pumps. A high-fidelity CFD model was developed using ANSYS Fluent to simulate internal flow dynamics, pressure distribution, and turbulence within the pump. The CFD results were used to identify critical wear points and pressure variations. A Neural Network model was then trained on historical performance data to predict degradation trends based on flow rate, pressure, temperature, noise, and vibration. Results showed that the integrated CFD-NN approach improved the accuracy of performance degradation estimation by 15% compared to traditional empirical models. The proposed method provides a robust framework for predictive maintenance and performance optimization in hydraulic systems. المستخلص: تعتبر المضخات المحورية ذات المكابس مكونات حاسمة في الأنظمة الهيدروليكية، وتشتهر بكفاءتها العالية وقدرتها على العمل في ظروف الضغط العالي. ومع ذلك، يظل تدهور الأداء بمرور الوقت بسبب أوجه القصور في الأجزاء الداخلية، مثل التآكل والتسرب والتجويف، تحديًا كبيرًا، تقترح هذه الورقة نهجًا مشتركًا باستخدام ديناميكيات الموائع الحسابية (CFD) وطرق الشبكات العصبية (NN) لتقدير تدهور أداء المضخات المحورية ذات المكابس. تم تطوير نموذج CFD عالي الدقة باستخدام برنامج ANSYS Fluent لمحاكاة ديناميكيات التدفق الداخلي وتوزيع الضغط والاضطراب داخل المضخة. تم استخدام نتائج CFD لتحديد نقاط التآكل الحرجة وتغيرات الضغط. ثم تم تدريب نموذج شبكة عصبية على بيانات الأداء التاريخية للتنبؤ باتجاهات التدهور بناءً على معدل التدفق والضغط ودرجة الحرارة والضوضاء والاهتزاز. أظهرت النتائج أن النهج المتكامل CFD-NN حسّن دقة تقدير تدهور الأداء بنسبة 15٪ مقارنة بالنماذج التجريبية التقليدية. يوفر الطريقة المقترحة إطارًا قويًا للصيانة التنبؤية وتحسين الأداء في الأنظمة الهيدروليكي